2019
DOI: 10.3892/ol.2019.10341
|View full text |Cite
|
Sign up to set email alerts
|

Novel imidazo[1,2‑a]pyridine inhibits AKT/mTOR pathway and induces cell cycle arrest and apoptosis in melanoma and cervical cancer cells

Abstract: The present study aimed to investigate the anti-cancer activity of imidazo[1,2-a]pyridine 5–7 in the A375 and WM115 melanoma and HeLa cervical cancer cell lines. The viability of cancer cells was analyzed by the MTT assay. Apoptosis was quantified by flow cytometry following staining of the cells with AnnexinV/propidium iodide (PI). The cell cycle was evaluated by flow cytometry after staining of cells with PI. The three compounds inhibited the proliferation of all cells for half maximal inhibitory concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…The increases in the levels of p21 cell cycle regulator and cyclin D1 are commonly used as a markers for cell cycle arrest at the G1 stage (Aliwaini et al, 2019;Benzeno et al, 2004). Our results are similar to many previous studies which have indicated that the treatment of various cell lines (such as; Breast cancer, Human hepatocellular carcinoma, Liver cancer, Lung cancer, Melanoma, HeLa cervical cancer) by IPs-based compounds (e.g.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The increases in the levels of p21 cell cycle regulator and cyclin D1 are commonly used as a markers for cell cycle arrest at the G1 stage (Aliwaini et al, 2019;Benzeno et al, 2004). Our results are similar to many previous studies which have indicated that the treatment of various cell lines (such as; Breast cancer, Human hepatocellular carcinoma, Liver cancer, Lung cancer, Melanoma, HeLa cervical cancer) by IPs-based compounds (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…Our results are similar to many previous studies which have indicated that the treatment of various cell lines (such as; Breast cancer, Human hepatocellular carcinoma, Liver cancer, Lung cancer, Melanoma, HeLa cervical cancer) by IPs-based compounds (e.g. IP-Se-05; P-Se-06; contributed in a cell cycle arrest in the G1 and G2 cell cycle stage, as well as elevated concentrations of p21, p53 proteins and cyclin D1 (Lee et al, 2013;Jung et al, 2013;Hayakawa et al, 2018;Aliwaini et al, 2019). In the current study, IP-5 compound has been proven to carry out its cytotoxic effect by triggering extrinsic apoptosis as evident by the high level of PARP cleaved, Caspases 7 and Caspases 8.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increasing γ -H2AX levels clearly indicated DNA fragmentation after treatment of glioblastoma cells with IP-Se-06. The observations by Aliwaini and collaborators [ 15 ] suggest that imidazopyridines may induce apoptosis through p53 regulation. In additions, our results corroborate those of Wang and collaborators [ 13 ], showing that novel imidazopyridine derivatives can exert anticancer activity by inducing mitochondrial pathway-mediated apoptosis and indicating such compounds as promising candidates for glioblastoma treatment [ 46 ] [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ability of imidazo[1,2- a ]pyridine derivatives to inhibit Akt pathway and cell cycle progression in cancer cells has been recently reported. Aliwaini and collaborators [ 15 ] described that imidazo[1,2- a ]pyridine induces cell cycle arrest and apoptosis, while it is able to inhibit Akt/mTOR pathway in melanoma and cervical cancer cells. Yu and collaborators [ 14 ] demonstrated the biological effects of imidazo[1,2- a ]pyridine derivatives on the PI3K/mTOR dual inhibition, resulting in a significant inhibition of tumor growth in colorectal carcinoma xenografts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation